Peningkatan Kualitas Lingkungan Daerah Aliran Sungai Solo Berbasis Interactive Participation - Rr Diah Nugraheni Setyowati (Jurnal Poli-Teknologi, 2020)
The river has a strategic role as a buffer for people's life so that the quality of the river affects surrounding environment. The development in various fields was a change in land use and environmental damage that caused a decrease in the hydrological function of the watershed and a decrease in environmental quality. The decline in environmental quality has not received special attention from both the government and the surrounding community, therefore an effort to improve the quality of the environment based on interactive participation is needed. The method used in this research is descriptive qualitative, so that in the analysis of problems and making models which are the final results of the study will be based on qualitative analysis. The research phase starts with the identification of the problem, then continues the process of collecting primary and secondary data. After the data is fulfilled, an analysis process is carried out which results in a simple design of an interactive participation-based community empowerment model. Based on the results of data analysis, the Solo DAS is in a critical condition, where the conditions describe the number of hydrological disasters that occurred. Land use in Solo watershed has changed, currently, the land is dominated by rice fields (irrigation and rainfed), gardens, fields and settlements. The maximum daily rainfall in Solo watershed is around 73 - 186 mm/ day, supported by relatively flat landforms, so it can be concluded that the Solo watershed is a flood-prone area. From the results of data analysis, it was also found that the higher the level of education, the higher the level of awareness in maintaining and improving the quality of the environment. The level of community education in the Solo DAS is quite good, so that appropriate community empowerment is interactive participation. The great opportunity for the community to be directly involved shows that the appropriate model of interactive participation empowerment is the Bottom Up model.